Effectiveness of Implementing the Regional Government Information System (SIPD) Application on the Preparation of Financial Reports at the Regional Revenue Agency Badung Regency - Darmayanti, Ida Ayu Made Dwi Astuti; Dewi, Nyoman Diah Utari; Widnyani, Ida Ayu Putu Sri (Jurnal Scientia, 2024)
Multiple factors connected to the installation and influence of the Regional Government Information System (SIPD) on Badung Regency Regional Revenue Agency financial report production prompted this investigation. SIPD should improve financial report preparation efficiency. The procedure should be faster and more accurate using automation and data integration. The Badung Regency Regional Revenue Agency was used to illustrate SIPD implementation locally. The study examines the Effectiveness of the Implementation of the Regional Government Information System Application (SIPD) on the Preparation of Financial Reports at the Badung Regency Regional Revenue Agency and the driving and inhibiting factors in its implementation. Study results show that the Regional Government Information System (SIPD) in Improving Regional Financial Reporting at Badung Regency Regional Financial and Asset Management Agency, Bali Province, was ineffective. The author's analysis using Duncan's effectiveness theory in Richard M. Steers shows that SIPD has not been able to significantly change the BAPENDA Badung Regency financial report's procedure, socialization, and increasing capability indicators. Therefore, SIPD in BAPENDA Badung Regency is not totally effective. The Badung Regency Financial and Asset Management Agency's Regional Government Information System (SIPD) Implementation to Improve Financial Reports faces other challenges. However, Bali Province's Badung Regency Financial and Asset Management Agency has worked to improve Regional Government Information System implementation.